2007
DOI: 10.1001/archinte.167.17.1827
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the Prevention, Diagnosis, and Treatment of Malaria in Human Immunodeficiency Virus–Infected Adults in Sub-Saharan Africa

Abstract: Background: Many countries in sub-Saharan Africa currently report high prevalences of both human immunodeficiency virus (HIV) and Plasmodium falciparum malaria. The likelihood of HIV-malaria coinfection may affect clinical management of patients. The extent to which standard clinical guidelines address HIV-malaria coinfection is unclear. Methods:We reviewed standard World Health Organization and other guidelines for diagnosis and treatment of malaria and/or HIV-related illness. We also searched PubMed (1990 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 99 publications
0
32
0
Order By: Relevance
“…These facts highlight the importance of assessing any malaria-induced disturbances in the laboratory prior to deciding how to manage HIV positive individuals. This approach can avoid the misdiagnosis of ARV failure or even the premature initiation of therapy (Brentlinger et al 2007). Unfortunately, access to ARV is not yet universal, either in Mz (INSIDA 2009) or in other African countries, whereas antimalarials drugs are currently accessible for the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These facts highlight the importance of assessing any malaria-induced disturbances in the laboratory prior to deciding how to manage HIV positive individuals. This approach can avoid the misdiagnosis of ARV failure or even the premature initiation of therapy (Brentlinger et al 2007). Unfortunately, access to ARV is not yet universal, either in Mz (INSIDA 2009) or in other African countries, whereas antimalarials drugs are currently accessible for the population.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + T cell counts have been implicated in Plasmodium control (Brentlinger et al 2007, Idemyor 2007, because these cells are negatively correlated with PD (Withworth et al 2000. However, we did not observe any association between these parameters, perhaps because of the study sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Co infection does not require changing the therapeutic protocol compared to the treatment of uncomplicated malaria and severe malaria, which is shared by Brentlinger [34], although for some authors a delay was found in the clearance of parasite in patients infected with HIV and treated with artemisinin, suggesting a metabolic disorder of antimalarials according to the immunological profile of the host [35].…”
Section: Therapeutic Profilementioning
confidence: 99%
“…6 Human immunodeficiency virus (HIV)-infected persons are at increased risk of clinical malaria compared with HIVuninfected persons and have a poorer response to antimalarial drugs in some studies. [7][8][9][10] The HIV increases the risk of maternal parasitemia during pregnancy 11 and of congenital malaria in the infant. 12 Although congenital malaria is uncommon, it has been associated with poor maternal antibody response to malaria antigens in HIV-positive women.…”
Section: Introductionmentioning
confidence: 99%